Improving livestock production efficiencies presents a major opportunity to reduce sectoral greenhouse gas emissions. (September 2016) - Hyland, J.J.; Styles, D.; Jones, D.L.; Williams, A.P.
Abstract: The livestock sector is under considerable pressure to reduce greenhouse gas (GHG) emissions. Repeated measurements of emissions over multiple years will indicate whether the industry is on course to successfully meet emission reduction targets. Furthermore, repeated analyses of individual farm emissions over different timeframes allow for a more representative measure of the carbon footprint (CF) of an agricultural product, as one sampling period can vary substantially from another due to multiple stochastic variables. To explore this, a CF was measured for 15 livestock enterprises that had been assessed three years previously. The aims of the research were to: (1) objectively compare CFs between sampling periods; (2) assess the relationship between enterprise CF and input efficiency; (3) use scenario analyses to determine potential mitigation measures. Overall, no significant difference was detected in beef and lamb enterprise CFs between the two sampling periods. However, when all observations were pooled together, the lowest-emitters were found to have more efficient systems with higher productivity with lower maintenance "overheads", compared with their higher-emitting counterparts. Of significance, scenario analyses revealed that the CF of beef and lamb could be reduced by 15% and 30.5%, respectively, if all enterprises replicated the efficiency levels of the least-emitting producers. Encouraging and implementing efficiency gains therefore offer the livestock industry an achievable method of considerably reducing its contribution to GHG emissions. Highlights: The livestock sector is under pressure to reduce greenhouse gas emissions. The carbon footprints of 15 farms were retaken three years after first being assessed. Significant differences were noted between the highest and lowest-emitting farms. Efficiency improvements could reduce the footprint of beef by 15% and lamb by 30.5%. This presents significant opportunities to reduce sectoral emissions.